Implementasi Upaya Pemulihan Aset Korban Kejahatan Tindak Pidana Penipuan dan Pencucian Uang Dalam Kasus First Travel - Irwan, Tania (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2021)
Assets resulting from criminal acts are the purpose of carrying out criminal acts with economic motives and thus eliminating access and rights of perpetrators to the proceeds of crime and their acquisition can be an effective way of eradicating economic-motivated criminal acts. The anti-money laundering regime in Indonesia has given birth to a new approach that is no longer focused on the perpetrators of crime but on the assets resulting from their crimes, known as the follow the money method. In addition, the law enforcement instruments against illegal assets contained in the Money Laundering Law are actually sufficient to achieve not only assets resulting from criminal acts but also to their acquisition. Ideally, the assets resulting from the crime are returned to the victims of the crime through a court decision with permanent legal force ordering the seizure of assets for the state or returning them to those who are entitled. However, this cannot be seen from First Travel's decision which sentenced the Defendants to imprisonment and confiscated First Travel's assets for the state, which did not immediately solve the problem because this decision did not reach out to the recovery of the impact of the crime experienced by the actual victim.